A review of synthesis graphene oxide from natural carbon based coconut waste by Hummer's method. (2023) - Omar, H.; Malek, N.S.A.; Nurfazianawatie, M.Z.; Rosman, N.F.; Bunyamin, I.; Abdullah, S.; Khusaimi, Z.; Rusop, M.; Asli, N.A.
Abstract: Coconut shell is an agricultural residue usually disposed of through open burning, which has a good potential as an alternative material to synthesize into nanomaterials. The production of carbon from natural sources can overcome the hazardous effect and reduce the risk of pollution. Researchers have developed a method by using coconut shell due to renewable waste product to produce new natural carbon source. This review has focused on research carried out on coconut shell powder (CSP) turn to natural graphite or activated carbon with high carbon content from various region worldwide. Graphene oxide (GO) based on natural graphite coconut shell powder was successfully synthesized with high scale using a modified Hummers method, and the obtained GO was confirmed using X-ray diffraction, Fourier transform infrared spectroscopy, Scanning electron microscopy, and Raman Spectroscopy.